Analisis Peraturan Daerah Daerah Istimewa Yogyakarta Nomor 1 Tahun 2022 Tentang Pendidikan Pancasila Dan Wawasan Kebangsaan - Irvansyah Irvansyah; Joko Widarto; Markoni Markoni; Achmad Edi Subiyanto (Social Science Academic, 2024)
This thesis presents an in-depth legal analysis of the Regional Regulation of the Special Region of Yogyakarta Number 1 of 2022 concerning Pancasila Education and National Insight and the influence of the PDI Perjuangan Faction of the Yogyakarta Special Region DPRD in the formation of the Regional Regulation. This normative legal research uses a conceptual approach that provides an explanation of the ideas of experts regarding the formation of the Regional Regulation. In order to provide the most accurate research results possible, a case approach was also carried out and even interviews were conducted. The results of the study show that the driving factors for the formation of the regional regulation are (a) providing legal certainty, (b) forming the character and identity of human resources, (c) creating harmony and harmony in the conditions of society, and (d) strengthening public awareness of the urgency of national and state life. The influence of the PDI Perjuangan Faction in question is very strong. In addition to being the Chairperson of the Commission, it is also the faction with the largest number of members, especially since the Sinau Kebangsaan Program was started with Kesbangpol throughout the DIY region. And after becoming a regional regulation, it was echoed through the internalization of Pancasila values. However, the success of this regulation is highly dependent on implementation and evaluation in the field.